EVALUASI KENAIKAN BERAT BADAN PADA BALITA STUNTING YANG DIBERIKAN PMT LOKAL DI PUSKESMAS LENGKONG KECAMATAN LENGKONG KABUPATEN NGANJUK - Setyowati, Anis (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2026)
Stunting is a chronic nutritional problem characterized by stunted linear growth and risks affecting long-term child development. One intervention effort is the provision of locally sourced complementary foods (PMT). This study aims to determine the weight gain of stunted toddlers receiving local PMT in the Lengkong Community Health Center (Puskesmas) area of Nganjuk Regency. The research design used was descriptive, using secondary data collection techniques from a cohort of toddlers. The study sample consisted of stunted toddlers aged 24-59 months who met the inclusion criteria. Data were collected from the toddler cohort and analyzed using frequency distribution. The results showed that 37 toddlers (97.4%) gained weight after receiving local PMT, while 1 toddler (2.6%) did not gain weight but maintained their weight. The conclusion of this study is that the provision of local PMT contributes to improving the nutritional status of stunted toddlers and is expected to be used as a strategy for stunting mitigation at the primary health care level.